Pengaruh Kompos Jerami Padi terhadap Kelarutan Ferro (Fe2+) dan pH Tanah Serta Pertumbuhan Tanaman Padi Ciherang di Tanah Sulfat Masam - Muhammad Suriani; Muhammad Mahbub; Rodinah Rodinah (Agroekotek View, 2020)
One type of land in a swamp ecosystem that has a lot of complexity is acid sulfate soils. One of the factors that can improve the condition of this soil is the use of organic material which functions to maintain soil redox and can chelate Fe2+. The purpose of this research was to know the effect of rice straw compost on ferro-iron solubility, soil pH, and rice growth so it obtained the appropriate treatment of the dose of rice straw compost. Soil sampling of acid sulfate soil was collected in Jejangkit District, South Kalimantan. This research was conducted in the greenhouse of Agroecotechnology Study Program and set up with a completely randomized design with a single factor. The treatments were K0: control, K1: soil + straw compost 2,5 t ha-1, K2: soil + straw compost 5,0 t ha-1, K3: soil + straw compost 7,5 t ha-1, K4: soil + straw 10,0 t ha-1, with 3 replications. The results showed that the dose of straw compost treatments was not significantly affected on Fe2+ iron solubility, number of tiller, wet and dry weight of rice plant, but showed a significant on soil pH. The best treatment of rice straw compost is in the treatment with 5 t ha-1 of dose because it can increase the highest pH of 3,72 and can reduce Fe2+ content to 54,82 mg kg-1. Tiller number, wet weight, and dry weight of rice plants were not significantly different because the plant runs into a limitation of growing.